Gambaran Penyediaan Fasilitas Belajar oleh Orangtua di Taman Pendidikan Alquran (TPA) Jorong Bonjo, Kenagarian Panampuang, Kecamatan IV Angkek, Kabupaten Agam - Erika Susanti; Syafruddin Wahid (Universitas Negeri Padang, 2018)
This research is motivated by the success of parents in the Taman Pendidikan Alquran (TPA) Jorong Bonjo, this is seen from the provision of learning facilities by parents at home. The purpose of this study is to describe the provision of learning facilities by parents at home in terms of study space, learning atmosphere, and learning aids. The type of this research is quantitative descriptive research. The population in this study is the child's parents. The sampling technique in this research is cluster random sampling from entire population. Data collection techniques used are questionnaires, while the data collection tool questionnaire. Technique of data analysis by using formula of percentage. From the results of the study showed that: the availability of study space by parents in the learning process of children at home, realization of a comfortable learning by parents in the process of learning at home, the availability of learning aids by parents in the process of learning children at home.Keywords: Study Room, Learning Atmosphere, Learning Aids